Implementation of Quality Filter Mapping (QFM) in Hot Press Using Lean Manufacturing To Eliminate Waste - Muhamad Yasin; Lukmandono (Procedia of Engineering and Life Science, 2021)
PT Sakari Sumber Abadi is a manufacturing company that is engaged in producing plywood products as its main product. This company has waste in the production line, namely in the 4.6 mm Birch product, including shrinkage putty, press mark, tip delemination, bubbles, ripping. Whereas for 18 mm Birch products, among others, press marks, putty shrinkage, concave, overlap, putty face too wide, ripping, waste in the face and delamination of the ends. What you want to achieve in this research is to eliminate the waste of 4.6 mm Birch Products and 18 mm Birch Products found in the Hot Press section in order to fulfill customer demand with the Lean Manufacturing approach. Lean Manufacturing is a systematic approach that eliminates waste and transforms processes. The results of the inspection using the Quality Filter Mapping (QFM) method obtained the largest waste in the Birch 4.6 mm Face 0.5 mm product, namely Failure to Riject by 0.82% and on Birch 18 mm Face 0.28 mm product, namely Failure to Riject by 7.1%. Recommendations for improvement include standard parameters of temperature, press time and pressure.